Automation of Code Development for Custom Workflow Applications to Improve Sustainability Factors of Technological Startups - Roy Choudhury, Joydeep (Digital Repository of Theses, 2025)
Startups face sustainability risks particularly due to Technical Debt (TD). TD is a metaphor to describe the shortcuts taken, resulting in the buildup of suboptimal designs and implementation choices made to meet short-term goals. Factors like team attrition, tight deadlines and resource constraints can amplify TD. TD leads to higher maintenance costs and reduced performance, often culminating in project failure for software startups. Our study explores custom code generation (CCG) as a strategy for reducing TD and preserving institutional memory while improving quality of the product, thereby enhancing sustainability of startups. In this research, structured interviews were conducted to understand the familiarity with the topic among founders, technologists, project managers, business development executives, technology users and educationists to assess their perception of using CCG to address the issue of TD. We designed a 22-question questionnaire to guide our one-on-one interviews. After explaining our concept, we documented participant responses using Google Forms. We employed quantitative analysis to draw conclusions from the collected data. The results indicate that of code generators have been used by 31% of the participants and current utilization of CCG as a strategy is low at 17.43%. However, about 70% participants agree that CCG is worthy of the effort, time and investment for the endeavour. Albeit, additional resources need to be committed initially for long term benefits of the projects. The average rating participants gave 7.987 out of 10 to the concept of using CCG to improve startup sustainability. The benefits of developing a CCG far outweigh code written manually. CCG can facilitate the reduction in manpower requirements, turnaround times, pivoting away from current requirements / implementation while eliminating the dependency on a very skilled team. Additionally, it can help preserve institutional knowledge by capturing and codifying best practices. By automating repetitive tasks, enforcing coding standards and capturing best practices, CCG can reduce manpower and development time, improve code quality, mitigate knowledge loss, enhance developer productivity and reduce technical debt. CCG can streamline development processes, mitigate risks and accelerate time-to-market, making it a valuable asset for startups to achieve their business objectives. CCG can emerge as a significant strategy for reducing technical debt, thereby enhancing the sustainability factors of technology startups.